Bacterial diversity in microbial mats and sediments from the Atacama Desert - Rasuk, Maria Cecilia (2015)
The Atacama Desert has extreme environmental conditions that allow the development of unique microbial communities. The present paper reports the bacterial diversity of microbial mats and sediments and its mineralogical components. Some physicochemical conditions of the water surrounding these ecosystems have also been studied trying to determine their influence on the diversity of these communities. In that way, mats and sediments distributed among different hypersaline lakes located in salt flats of the Atacama Desert were subjected to massive parallel sequencing of the V4 region of the 16S rRNA genes of Bacteria. A higher diversity in sediment than in mat samples have been found. Lakes that harbor microbial mats have higher salinity than lakes where mats are absent. Proteobacteria and/or Bacteroidetes are the major phyla represented in all samples. An interesting item is the finding of a low proportion or absence of Cyanobacteria sequences in the ecosystems studied, suggesting the possibility that other groups may be playing an essential role as primary producers in these extreme environments. Additionally, the large proportion of 16S rRNA gene sequences that could not be classified at the level of phylum indicates potential new phyla present in these ecosystems.